Implications of Deep Meaningfulness for Sustainability: Reimagining the Literature on Vocational Calling - Wolfgang Bichler-Riedl; Stefan Gold (Sustainable Development, 2025)
Decent work is a pivotal aspect of sustainable development. However, recent developments suggest that precarious work is rising. This is particularly true for prosocial workers who exhibit extraordinary self-sacrifice despite working in detrimental conditions. In this manuscript, we shed light on how the individual sensemaking of called prosocial workers impacts the sustainability of professions. We achieve this by appropriating escalation of commitment determinants to meaningful careers. This reveals how enrichment and devaluation are necessary to maintain callings in precarious conditions that prevent the achievement of those callings' goals. Accordingly, we argue that following one's calling can significantly increase the psychological sustainability of one's career in the short term but decreases the sociological sustainability of one's profession in the long term. Based on our review, we discuss potential avenues for de-escalation, the responsibilities of the current status of meaningful yet precarious professions, and implications for sustainable development.
Keywords: 330; decent work; deeply meaningful work; escalation of commitment; precarious work; sustainable labor markets; vocational calling